Effects of the use of powdered demineralized allograft on the periodontal indexes on the distal surface of second molars after lower third molar surgery - Sayed Mehdi Ghoreishian; Dariosh Hasheminia; Alireza Heidarynasab (Isfahan University of Medical Sciences, 2012)
Introduction: Several studies have evaluated the effect of surgical removal of the impacted lower third molars on periodontal lesions around the adjacent second molars and the recovery of these lesions. The aim of this study was to evaluate the effect of demineralized bone protein on the recovery of periodontal lesions after third molar surgery in patients referring to the Department of Oral and Maxillofacial Surgery, Isfahan Faculty of Dentistry. Materials and Methods: In this single-blind clinical trial, 16 patients referring to the Department of Oral and Maxillofacial Surgery, who were candidates for the bilateral surgical removal of lower third molars, were randomly selected. Inclusion criteria consisted of the lower third molar impaction and presence of second lower molars, and a mean age of 26 years. Pocket depths and attachment levels on the distal surface of second molars were measured in the case and control groups before surgery and 12 weeks post-operatively. Data in relation to means of changes were analyzed by paired t-test using SPSS software (α = 0.05). Results: The results of this study showed statistically significant differences in pocket depths and attachment levels before surgery and 12 weeks post-operatively each group (p value < 0.001). According to paired t-test there were no statistically significant differences in pocket depths (p value = 0.497) and attachment levels (p value = 0.155) between the two groups 12 weeks post-operatively. Conclusion: Under the limitations of the present study, use of demineralized bone protein had no effect on periodontal parameters after surgical removal of impacted lower third molars. Key words: +.